UML 2.0 in action : a project based tutorial - Grässle, Patrick; Baumann, Henriette; Baumann, Philippe (From technologies to solutions., 2005)
"This book is designed to be read while you work on a real project. After an initial review of the essentials of UML and the design process, it begins with the modeling of a business system and its business processes, in this case an airport. Then the IT system intended to serve that business process is described and analyzed. Finally the integration of the system into the production environment is covered in detail. The book can be used in two ways: it can be read through as a thorough grounding in how UML really works in practice; in addition it can be used as stand alone guide to that particular aspect of your own project. Both result in an intuitive understanding of how to actually use UML."--Resource description page